2019
DOI: 10.1111/1471-0528.15858
|View full text |Cite|
|
Sign up to set email alerts
|

Patterns of hysterectomy in India: a national and state‐level analysis of the Fourth National Family Health Survey (2015–2016)

Abstract: Objective The National Family Health Survey‐4 in India provided the first nationally representative estimates of hysterectomy among women aged 15–49. This paper aims to examine the national and state‐level age‐specific prevalence of hysterectomy, individual and household level factors associated with the procedure, and state‐level indicators that may explain variation across states. Design Cross‐sectional, nationally representative household survey. Setting National Family Health Survey was conducted across al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
42
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 28 publications
3
42
0
2
Order By: Relevance
“…Excessive bleeding or pain was the most common reason for hysterectomy (56%), and the index study also has the indication of abnormal bleeding and pain abdomen as the common indications. It was found that more rural women in the age group 45-49 years were predisposed to undergo hysterectomy especially those without schooling, high parity and those living in east and south India (Desai et al, 2015) and this is consistent with the present study. This could be in turn due to either lack of awareness among these rural women or an unwillingness for a followup, thus getting subjected to an unnecessary procedure.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Excessive bleeding or pain was the most common reason for hysterectomy (56%), and the index study also has the indication of abnormal bleeding and pain abdomen as the common indications. It was found that more rural women in the age group 45-49 years were predisposed to undergo hysterectomy especially those without schooling, high parity and those living in east and south India (Desai et al, 2015) and this is consistent with the present study. This could be in turn due to either lack of awareness among these rural women or an unwillingness for a followup, thus getting subjected to an unnecessary procedure.…”
Section: Discussionsupporting
confidence: 92%
“…However, leiomyoma has remained the leading factor leading to hysterectomy in most of the cases, but with an increas-ing trend towards an acceptance of other conservative options. The NFHS-4 survey listed the prevalence, indications and trends of hysterectomy in India for the irst time (Desai et al, 2015). From the numbers obtained, it was analysed that India could be the country with the maximum number of hysterectomies.…”
Section: Introductionmentioning
confidence: 99%
“…The negative association between membership of the RSBY scheme and CS and lack of association with hysterectomy and CS surgery and the state insurance scheme, also found in other studies, 30 remains puzzling given that both form part of the respective insurance packages. One explanation is that since RSBY is largely a scheme for the poor, the negative effect of lower income over-ride any positive impact of holding insurance.…”
Section: Discussionmentioning
confidence: 64%
“…Hysterectomy for benign diseases is the most common gynaecological surgery performed worldwide [ 1 , 2 ]. According to the National Family Health Survey (NFHS 4 survey 2015-16), in India, 6% of women in the age group of 30-49 years had undergone hysterectomy for heavy menstrual bleeding or chronic pelvic pain (56%), followed by fibroids (20%) [ 3 ].…”
Section: Introductionmentioning
confidence: 99%